PEMANFAATAN METODE 3B (BERNYANYI DAN BERMAIN SECARA BERKELOMPOK) TERHADAP PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI DI SPS DAHLIA 55 KALISAT – JEMBER TAHUN AJARAN 2024/2025 - Kamiliatul Amalia; Ahmad Afandi; Wedya Puspita; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the fun approaches that suits the characteristics of early childhood is the 3B method (Singing and Playing in Groups), which is believed to improve children's memory through activities involving rhythm, movement, and social interaction. The purpose of this study was to determine how the use of the 3B method can support the development of early childhood memory. The research method used was a qualitative approach with the research subjects being group B children at SPS Dahlia 55. Data were collected through observation, interviews, and documentation. The data analysis technique used the Miles and Huberman model which includes: data reduction, data presentation, and drawing conclusions/verification. The final results of this study indicate that the 3B method has a positive influence in improving early childhood memory, indicated by the increased ability of children to convey information and experiences coherently and meaningfully.